The Translation of Metaphor from the Novel Beastly into Beastly, Beauty and the Beast Abad 21 - Ayu Widyari, Ni Nyoman; Putra Yadnya, Ida Bagus; Seri Malini, Ni Luh Nyoman (Udayana Journal of Social Sciences and Humanities; Vol 4 No 1 (2020): UJoSSH, February 2020DO - 10.24843/UJoSSH.2020.v04.i01.p05, 2020)
The translation is a written medium and useful connection to communicate with other people in a different language, culture, and background. Figurative language is widely used in any form of communication, such as in daily conversations, advertisements, articles in newspapers, novels, poems, etc. Figurative language often provides more effective means of saying what can be meant than a direct statement. This writing is aimed at finding out the types of metaphors in translating the novel of Beastly based on the theory of Kovecses. The analysis was presented in the form of words and sentences. The result of this study showed that the use of a structural metaphor was mostly used in this study based on the data in the novel Beastly. The structural metaphor occurred as the source domain provides a relatively rich knowledge structure for the target or language concept.